A test and improvement method for creep characteristics of 409L stainless steel welded joints
By adding Ce and Ti elements to the 409L stainless steel welded joints and using ER304 austenitic stainless steel as the filling material, the problem of creep rupture of the welded joints under high temperature and cyclic stress conditions is solved, and the creep life and minimum creep are significantly improved. Variable speed, extending the service life of automobile exhaust manifolds.
Patent Information
- Application Number
- CN202010836561.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-08-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-08-19
AI Technical Summary
The 409L stainless steel welded joints are prone to creep fracture under high temperature and cyclic stress conditions, resulting in a shorter service life of the automobile exhaust manifold. The existing research focuses on expensive austenitic stainless steel rather than inexpensive ferrite stainless steel.
The ER304 Austeen Stainless Steel is used as the filling material, and the percentage of the mass percentage of the welding wire is added during welding. Its creep characteristics and optimize the design of the welding joint.
By adding CE and TI elements, the 409L stainless steel welding connector has been significantly increased and the minimum peristaltic rate of the 409L stainless steel welding joint has extended the service life of the automotive exhaust manifold, and provided theoretical and data support for the widespread application of 409L stainless steel.
Smart Images

Figure CN112098243B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a creep property test and an improvement method for a welded joint, in particular to a creep property test and an improvement method suitable for a 409L stainless steel welded joint, and belongs to the technical field of welding. Background Art
[0002] Ferritic stainless steel (400 series) contains 15% to 30% chromium and has a body-centered cubic crystal structure. This type of steel generally does not contain nickel, and sometimes contains a small amount of Mo, Ti, Nb and other elements. This type of steel has the characteristics of high thermal conductivity, low expansion coefficient, good oxidation resistance, excellent stress corrosion resistance, etc., and is mostly used to manufacture parts that are resistant to corrosion by the atmosphere, water vapor, water and oxidizing acids. Because ferritic stainless steel contains little or no nickel, it is called a resource-saving and environmentally friendly material in the industry.
[0003] 409L (Ferritic stainless steel, FSS) is a typical representative of low chromium nickel ferritic stainless steel. It is widely used in various high temperature and high pressure fields due to its advantages of high temperature oxidation resistance, small thermal expansion coefficient, energy saving and environmental protection, etc., and is especially often used in the manufacture of automobile exhaust manifolds. However, the welding of 409L ferritic stainless steel is prone to weld embrittlement and poor toughness at low temperatures. In addition, during the operation of the manifold, its temperature can reach 800℃~1000℃. With the continuous start or stop, speed up or slow down of the car, the manifold welding joint usually needs to experience hot and cold loads with large temperature difference or hot and cold loads with small temperature difference many times, which will cause creep behavior of the manifold welding joint weld. As the car is used for a long time, this creep behavior continues to accumulate, and eventually the exhaust pipe will suffer from creep fracture.
[0004] Creep is the phenomenon that the strain of solid materials increases with time under stress. On the one hand, creep is different from thermal fatigue. Thermal fatigue is the expansion and contraction of solid material parts when the ambient temperature changes sharply and repeatedly when the solid material parts work under high temperature conditions. If they are constrained, thermal stress (also known as temperature difference stress) will be generated inside the solid material parts. The thermal stress changes sharply and repeatedly with the ambient temperature, causing fatigue damage to the solid material. The research direction of thermal fatigue damage is based on the basis of "ambient temperature change", while the research direction of creep damage is based on the basis of "extending the time of stress". On the other hand, creep is different from plastic deformation. Plastic deformation usually occurs after the stress exceeds the elastic limit, while creep can also occur when the stress is less than the force applied by the elastic limit as long as the stress acts for a long time. Due to creep, the stress state of the material at a certain moment is generally related not only to the deformation at that moment, but also to the deformation process before that moment. Intergranular creep fracture is a major form of creep fracture of 409L ferritic stainless steel. This is mainly because under the action of high temperature and low stress for a long time, as creep continues, grain boundary sliding and grain boundary diffusion are relatively sufficient, which in turn promotes the formation and development of cracks along the grain boundaries.
[0005] The application areas of welded joints cannot be simply defined as applications under constant temperature and strain. Cyclic temperature has a great influence on the creep life of welded joints. Studies have shown that compared with isothermal environment, the cyclic stress response (CSR) generated under thermal cycling conditions is greater, and compared with creep-isothermal fatigue (Creep-IF), the higher stress relaxation and lower inelastic strain rate during the holding period of creep-thermomechanical fatigue (Creep-TMF) will lead to more significant creep damage; Similarly, the loading range, loading form and loading rate of stress and strain will have a great influence on the creep performance of welded joints. These influences are mainly manifested in the holding time, strain dwelling time and tensile holding force introduced at the stress peak; In addition, although some studies have verified that the use of in-phase (IP) and out-of-phase (OP) loading methods in thermomechanical fatigue (TMF) tests has no significant effect on the plastic deformation and life of the base material, this is not the case for welded joints. The typical dynamic strain aging (Dynamic strain The strengthening effect of the solid solution atoms of the DSA (Degradation of Stress Aging, DSA) effect on the fatigue and creep life of materials is inevitable in the in-phase-thermomechanical fatigue (IP-TMF) test, the out-of-phase-thermomechanical fatigue (OP-TMF) test, the isothermal fatigue (IF) test, and the thermomechanical fatigue (TMF) test, and a large number of tests have confirmed this. The loading methods of IP and OP will affect the strain rate of the material, the starting temperature of the DSA effect, and the creep stress relaxation phenomenon. In addition, Cr is an extremely important element in stainless steel. The content of Cr not only has a great influence on the corrosion resistance, high-temperature brittle transition temperature, and carbide formation of stainless steel welded joints, but also has a certain influence on the high-temperature creep resistance and high-temperature hardness of stainless steel welded joints.
[0006] Among the creep studies of the above welded joints, there are many records of creep studies on expensive welded joints such as 316L austenitic stainless steel, but there are few records of creep studies on cheap welded joints such as 409L ferritic stainless steel. The creep data of austenitic stainless steel welded joints often do not match the actual production of ferritic stainless steel welded joints. Creep fracture of the weld of the automobile exhaust manifold welded joint will cause inevitable potential harm to the car and the driver. Therefore, how to improve the creep characteristics of 409L stainless steel welded joints to obtain a smaller minimum creep rate and a longer creep life, and then on the one hand, it can achieve the extension of the service life of the automobile exhaust manifold including the 409L stainless steel welded joint, and on the other hand, it can provide theoretical and data support for seeking a wider range of uses for cheap 409L stainless steel to reduce material costs, which has practical significance. Summary of the invention
[0007] In view of the above problems, the present invention provides a creep property test and improvement method for a 409L stainless steel welded joint, which can be used to study the creep properties of the 409L stainless steel welded joint. On the one hand, it can extend the service life of the automobile exhaust manifold including the 409L stainless steel welded joint. On the other hand, it can provide theoretical and data support for seeking a wider range of application fields for cheap 409L stainless steel to reduce material costs.
[0008] To achieve the above purpose, the test method for creep properties of 409L stainless steel welded joints is to conduct a long-term creep test under high temperature range of 520-580°C and large cyclic stress conditions of 80-140MPa, specifically including the following steps:
[0009] Step 1, sample preparation: using austenitic stainless steel as the filling material, two 409L stainless steel welding test plates are butt-welded and then cut to obtain the 409L parent material creep specimen required for the test; using the same welding process and cutting method to obtain the 409L creep specimen containing Ce and Ti;
[0010] Step 2: creep test: on a dynamic thermal simulator, OP and IP loading methods are used to perform a tensile test on the 409L parent material creep specimen until the 409L parent material creep specimen undergoes creep rupture; on a dynamic thermal simulator, OP and IP loading methods are used to perform a uniaxial tensile test on the 409L creep specimen containing Ce and Ti until the 409L creep specimen containing Ce and Ti undergoes creep rupture;
[0011] Step 3: Creep property analysis: The overall strain, minimum creep rate in the stable stage, and strain amplitude difference of 409L base material creep specimens and 409L creep specimens containing Ce and Ti under OP and IP loading methods are compared, including the DSA effect, thermal activation recovery process, fracture microstructure, fracture mode, grain boundary morphology, fracture precipitates, and Cr element flow characteristics.
[0012] In step 1, when two 409L stainless steel welding test plates are butt-welded, the joint has an I-shaped welding groove.
[0013] In step 1, the filling material is ER304 austenitic stainless steel.
[0014] In step one, the Ce and Ti elements of the 409L creep specimen containing Ce and Ti account for 0.26% and 1.04% of the welding wire mass respectively; the Ce and Ti elements are added in the form of nano-scale CeO2 and TiO2 respectively; the cross-section to be welded of the welding specimen is repeatedly cleaned with acetone before welding, and the weight of two welding specimens is weighed after the acetone evaporates, and an acetone solution containing a set mass of CeO2 and TiO2 is evenly applied to the cross-section to be welded, and welding is performed after drying. After welding is completed, the weight of the welding specimen welded as a whole is weighed, and the difference between the weight before and after welding is calculated, and then the set mass of CeO2 and TiO2 added is divided by the difference, respectively, to obtain a welding specimen in which the Ce and Ti elements account for 0.26% and 1.04% of the welding wire mass respectively.
[0015] A method for improving the creep properties of a 409L stainless steel welded joint is characterized in that ER304 austenitic stainless steel is used as a filling material for welding, and 0.26% and 1.04% of Ce and Ti elements are added to the welding wire by mass respectively.
[0016] A method for improving the creep characteristics of a 409L stainless steel welded joint, characterized in that, for a control device using a 409L stainless steel welded joint, its control mode is a mode that can put the 409L stainless steel welded joint in an actual working condition corresponding to an OP loading mode.
[0017] Compared with the existing technology, since the application field of welded joints cannot be simply defined as application under constant temperature and strain, the creep property test and improvement method of 409L stainless steel welded joints takes 409L ferritic stainless steel (FSS) as the research object, introduces the temperature range of 520-580℃ and the stress range of 80-140MPa, and uses the in-phase (IP) and out-of-phase (OP) loading methods to apply stress to the creep specimens, so as to study the creep property of 409L ferritic stainless steel (FSS) I type welded joints under large cyclic stress in a small range of high temperature and different loading methods. The creep behavior of 409L stainless steel welded joints was studied, and it was concluded that a smaller minimum creep rate and a longer creep life could be obtained under OP loading mode. At the same time, by adding Ce and Ti elements to the creep specimens before welding, it was concluded that Ce and Ti elements could significantly enhance the creep properties of 409L stainless steel welded joints. On the one hand, it can extend the service life of automobile exhaust manifolds including 409L stainless steel welded joints. On the other hand, it can provide theoretical and data support for seeking a wider range of uses for cheap 409L stainless steel to reduce material costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] FIG. 1( a ) is a front view of a creep specimen; FIG. 1( b ) is a top view of a creep specimen;
[0019] Figure 2 This is a schematic diagram of the installation of the creep specimen on the dynamic thermal simulator;
[0020] Figure 3(a) is the temperature-time curve of the sample test; Figure 3(b) is the stress-time curve of the sample test in IP loading mode; Figure 3(c) is the stress-time curve of the sample test in OP loading mode;
[0021] FIG4(a) is a time-strain curve of creep behavior of a creep specimen; FIG4(b) is a trend diagram of the time-strain amplitude difference Δε of creep behavior of a creep specimen under the same cyclic stress amplitude changing with time; FIG4(c) is a creep rate curve of a creep specimen;
[0022] FIG5(a) is a diagram showing the overall microscopic fracture morphology of a 409L parent material creep specimen under the OP loading mode; FIG5(b) is a diagram showing the dimple area of a 409L parent material creep specimen under the OP loading mode; FIG5(c) is a diagram showing the crack in the dimple of a 409L parent material creep specimen under the OP loading mode; FIG5(d) is a diagram showing the nucleation dimple and micropores of a 409L parent material creep specimen under the OP loading mode;
[0023] FIG6(a) is a diagram showing the overall microscopic fracture morphology of a 409L parent material creep specimen under IP loading mode; FIG6(b) is a diagram showing the cleavage zone of a 409L parent material creep specimen under IP loading mode; FIG6(c) is a diagram showing a small amount of dimples of a 409L parent material creep specimen under IP loading mode; FIG6(d) is a diagram showing oxides of a 409L parent material creep specimen under IP loading mode;
[0024] FIG7(a) is a diagram showing the overall microscopic fracture morphology of a 409L creep specimen containing Ce and Ti under OP loading mode; FIG7(b) is a diagram showing an equiaxed dimple of a 409L creep specimen containing Ce and Ti under OP loading mode; FIG7(c) is an enlarged diagram showing an equiaxed dimple of a 409L creep specimen containing Ce and Ti under OP loading mode; FIG7(d) is a diagram showing a crack of a 409L creep specimen containing Ce and Ti under OP loading mode;
[0025] FIG8(a) is a diagram showing the overall microscopic fracture morphology of a 409L creep specimen containing Ce and Ti under IP loading mode; FIG8(b) is a diagram showing the crack of a 409L creep specimen containing Ce and Ti under IP loading mode; FIG8(c) is a diagram showing the cleavage zone of a 409L creep specimen containing Ce and Ti under IP loading mode; FIG8(d) is a diagram showing the microcracks on the cleavage zone of a 409L creep specimen containing Ce and Ti under IP loading mode;
[0026] FIG9(a) is a diagram showing the grain boundary morphology and precipitate distribution of a 409L parent material creep specimen under IP loading mode; FIG9(b) is a diagram showing the grain boundary morphology and precipitate distribution of a 409L parent material creep specimen under OP loading mode; FIG9(c) is a diagram showing the grain boundary morphology and precipitate distribution of a 409L creep specimen containing Ce and Ti under IP loading mode; FIG9(d) is a diagram showing the grain boundary morphology and precipitate distribution of a 409L creep specimen containing Ce and Ti under OP loading mode;
[0027] FIG10(a) is an EDS analysis diagram of precipitates of a 409L parent material creep specimen under IP loading mode; FIG10(b) is an EDS analysis diagram of precipitates of a 409L parent material creep specimen under OP loading mode; FIG10(c) is an EDS analysis diagram of precipitates of a 409L creep specimen containing Ce and Ti under IP loading mode; FIG10(d) is an EDS analysis diagram of precipitates of a 409L creep specimen containing Ce and Ti under OP loading mode;
[0028] Figure 11(a) is a line scan EDS graph of the Cr element in the grain boundary precipitates in Figure 10(b); Figure 11(b) is a line scan EDS graph of the Cr element in the grain boundary precipitates in Figure 10(c); Figure 11(c) is a line scan EDS graph of the Cr element in the grain boundary precipitates in Figure 10(c); Figure 11(d) is a line scan EDS graph of the Cr element in the grain boundary precipitates in Figure 10(d). DETAILED DESCRIPTION
[0029] The present invention is described in detail below by taking the welding test of 409L (FSS) hot-rolled welding test plate as an example.
[0030] 1. Sample preparation
[0031] The test material is a 105mm×70mm×4mm 409L (FSS) hot-rolled welded test plate. Use sandpaper and files to grind and remove burrs and corners. Use TIG-200A inverter DC argon arc welding machine to weld the welded test plate. During welding, the two welded test plates are butt welded, and the joint is an I-shaped welding groove. The chemical composition of the 409L (FSS) plate is shown in Table 1. In order to obtain a 409L (FSS) welded joint with better plasticity, ER304 austenitic stainless steel with a diameter of 1.6mm is used as a filler material for welding. During welding, the heat input and cooling time are reasonably controlled to avoid the formation of a large amount of σ phase, which will cause embrittlement of the welded joint and affect the high-temperature creep performance of the welded joint. The chemical composition of ER304 austenitic stainless steel is shown in Table 2.
[0032] Table 1 Chemical composition of 409L ferritic stainless steel (mass percentage, wt.%)
[0033]
[0034] The welded steel plate was cut by a wire cutting machine to obtain the 409L parent material creep specimen required for the test, as shown in Figure 1(a) and Figure 1(b).
[0035] The applicant has previously prepared 14 groups of welded joint samples with different Ce and Ti contents to test the performance of 409L stainless steel welded joints, and conducted impact and tensile tests on them. The test results show that after adding Ce and Ti, the welded joints of 409L stainless steel can obtain better performance. This experiment also attempts to improve the creep properties of 409L stainless steel welded joints by adding Ce and Ti. In this test, Ce and Ti elements are added in the form of nano-scale CeO2 and TiO2, respectively. Before welding, the section to be welded of the welding sample is repeatedly cleaned with acetone. After the acetone evaporates, the weight of two welding samples is weighed, and the acetone solution containing the set mass of CeO2 and TiO2 is evenly applied to the section to be welded. After drying, welding is carried out. After welding is completed, the weight of the welding sample welded as a whole is weighed, and the difference between before and after welding is calculated. Then, the set mass of CeO2 and TiO2 added is divided by the difference, respectively, to obtain a group of welding test plates in which the Ce element and Ti element account for 0.26% and 1.04% of the welding wire mass percentage, respectively. Finally, the same welding process and cutting method are used to obtain 409L creep specimens containing Ce and Ti elements and good performance for creep testing.
[0036] 2. Creep test
[0037] The high temperature creep test was carried out on a DST-1000PC dynamic thermal simulator. The two ends of the 409L parent material creep specimen were fixed with chucks, and the thermocouple was spot welded to the center of the specimen. Figure 2 As shown, the heating current is set to 120A, the heating rate is set to 70℃ / min, the temperature range is set to 520~580℃, and the temperature-time variation curve is shown in Figure 3(a). OP and IP loading methods are used to apply 80~140MPa uniaxial stress to the specimen, and the direction is parallel to the specimen clamping direction. The loading stress-time variation curve is shown in Figure 3(b) and Figure 3(c). The test was carried out until the 409L parent material creep specimen creep fractured. The creep test results are shown in Figure 4(a) to Figure 4(c) shown.
[0038] The 409L creep specimens containing Ce and Ti were subjected to the above creep tests under the same test conditions. The creep test results are shown in Figure 4(a) to Figure 4(c) shown.
[0039] 3. Creep characteristics analysis
[0040] 3.1 Creep behavior
[0041] As shown in Figure 4(c), the creep rate of the 409L parent material creep specimen in the IP loading mode at each creep stage is greater than the creep rate in the OP loading mode. As shown in Figure 4(a), the creep rate and overall strain of the 409L parent material creep specimen in the IP loading mode are greater than those of the 409L parent material creep specimen in the OP loading mode. This shows that the 409L (FSS) welded joint can obtain a longer creep life, a lower minimum creep rate, and smaller creep damage under the OP loading mode. This phenomenon also exists in similar OP-TMF and IP-TMF tests. If the 409L stainless steel welded joint is only used as a component, such as an automobile exhaust manifold, its actual working condition is usually variable, and is usually sometimes in the actual working condition corresponding to the IP loading mode and sometimes in the actual working condition corresponding to the OP loading mode. When the 409L stainless steel welded joint is used as a control execution component, the 409L stainless steel welded joint can be placed in the actual working condition corresponding to the OP loading mode by artificially setting the control mode, thereby improving the creep characteristics of the 409L stainless steel welded joint. That is, for the control device using the 409L stainless steel welded joint, its control mode is a mode that can place the 409L stainless steel welded joint in the actual working condition corresponding to the OP loading mode. With such a setting, the 409L stainless steel welded joint can obtain a longer creep life and a lower minimum creep rate, as well as smaller creep damage.
[0042] Under the same test conditions, the creep life and minimum creep rate of 409L creep specimens containing Ce and Ti are better than those of 409L parent material creep specimens. The minimum rate of 409L creep specimens containing Ce and Ti using OP loading mode is 3.42um / h and the creep life is 96h. Compared with 409L parent material creep specimens under the same test conditions, the minimum creep rate of 409L creep specimens containing Ce and Ti decreased by 51.42% (OP loading mode) and 2.8% (IP loading mode), respectively, and the creep life increased by 10.34% (OP loading mode) and 21.43% (IP loading mode), respectively.
[0043] 3.2 DSA effect and thermally activated recovery
[0044] As shown in Figure 4(b), the trend of the strain amplitude difference Δε generated by the maximum stress and the minimum stress under the same stress amplitude changes with time. The Δε values of all the 409L parent material creep specimens and 409L creep specimens containing Ce and Ti in the test are significantly reduced at the end of the first stage of creep. This phenomenon is caused by initial creep hardening. In this experiment, a constant stress amplitude was set, and the initial hardening was manifested as a significant decrease in the Δε value at the end of the first stage of creep. The performance of applying a constant stress during hardening can be understood as a relative decrease in the Δε value during the persistent creep climb.
[0045] As shown in Figure 4(b), the strain amplitude difference rebounded quickly after a sudden drop, and this rebound was more significant in the 409L parent material creep specimen. This displacement and average strain mutation phenomenon during the cyclic deformation process is the macroscopic manifestation of the DSA effect. In addition, in all tests, the displacement and average strain mutation phenomenon caused by the DSA effect was extremely obvious in the late creep stage. As can be seen from Figure 4(b), the Δε mutation value of both the 409L parent material creep specimen and the 409L creep specimen containing Ce and Ti using the OP loading mode is higher than that of the corresponding IP loading mode. At the same time, the Δε mutation of the 409L parent material creep specimen and the 409L creep specimen containing Ce and Ti under the IP loading mode was delayed. When the 409L parent material creep specimen and the 409L creep specimen containing Ce and Ti under the OP loading mode were subjected to large tensile stress at temperatures of 520℃~550℃, their dislocation density continued to increase, and the DSA effect was greater than that of the IP loading mode. For example, the thermal activation recovery process of 316L austenitic stainless steel is more prominent in the temperature environment of 550℃~580℃. The dislocations generated in the 409L parent material creep specimens and 409L creep specimens containing Ce and Ti under IP loading mode are reordered and distributed, but due to the enhancement of its plane sliding dislocations in the DSA effect field, the limitation of screw dislocations weakens the thermal activation recovery process. It can be seen that compared with the IP loading mode, the larger DSA effect of the 409L parent material creep specimens and 409L creep specimens containing Ce and Ti under OP loading mode below 550℃ reflects a larger hardening degree, which reduces the lower limit of deformation displacement. The stronger thermal activation recovery process under OP mode above 550℃ promotes the cyclic softening phenomenon in the creep process and increases the upper limit of deformation displacement. Compared with the 409L parent material creep specimen, the Δε first mutation rate of the 409L creep specimen containing Ce and Ti showed a significant decrease (the IP mode decreased by 56.13%, and the OP mode decreased by 84.59%). After recovering, the development of the Δε value gradually stabilized. At this time, the creep characteristics showed cyclic softening and stability characteristics.
[0046] 3.3 Fracture microstructure analysis
[0047] The fracture microstructure of the 409L parent material creep specimen under OP loading mode is as follows: Figure 5(a) to Figure 5(d) As shown in Figure 5(a) and Figure 5(b), the fracture of the 409L parent material creep specimen using the OP loading mode is almost entirely composed of dimples, which show a more obvious sense of hierarchy and are significantly affected by oxidation. As shown in Figure 5(d), the rupture of the dimples is caused by nucleation and numerous micropores. As shown in Figure 5(c), after the dimple area is enlarged, it can be seen that there are obvious cracks, and the crack extension is a mixed fracture mode combining transgranular fracture and intergranular fracture.
[0048] The fracture microstructure of the 409L parent material creep specimen under IP loading mode is shown in Figure 2. Figure 6(a) to Figure 6(d) As shown. Figure 6(a) to Figure 6(d) As shown in the figure, the fracture of the 409L parent material creep specimen using the IP loading mode is a mixed fracture consisting of cleavage steps in the cleavage zone [Figure 6(b)], a large amount of oxides [Figure 6(d)], and a small amount of dimples [Figure 6(c)]. Compared with the fracture of the OP mode, the entire fracture does not have micropores, the necking morphology is not significant, and brittle fracture is dominant.
[0049] The fracture microstructure of 409L creep specimen containing Ce and Ti under OP loading mode is shown in Figure 2. Figure 7(a) to Figure 7(d) As shown in Figure 7(a), there are obvious cracks on the fracture surface of the 409L creep specimen containing Ce and Ti using the OP loading mode. The fracture presents a fracture mode with a large number of equiaxed dimples [Figure 7(b), Figure 7(c)] and crack oxides [Figure 7(d)]. The size and distribution of the dimples are more uniform than those of the 409L parent material creep specimen, and oxides exist in both the crack initiation and propagation areas.
[0050] The fracture microstructure of 409L creep specimen containing Ce and Ti under IP loading mode is shown in Figure 2. Figure 8(a) to Figure 8(d) As shown in the figure, the fracture of the 409L creep specimen containing Ce and Ti using the IP loading mode also has obvious cracks, but the size and number of cracks are significantly reduced [Figure 8(a), Figure 8(b)]. The crack initiation and propagation positions are also in the oxidation zone, and the fracture shows a mixed fracture mode of oxidation and cleavage [Figure 8(c)]. Further magnification of the cleavage zone shows that there are also many small cracks on the cleavage step surface [Figure 8(d)].
[0051] As mentioned above, regardless of whether Ce and Ti are contained, the fracture fluctuation degree of the 409L parent material creep specimen and the 409L creep specimen containing Ce and Ti loaded by OP mode is significantly greater than that of the 409L parent material creep specimen and the 409L creep specimen containing Ce and Ti loaded by IP mode, which is related to the creep time experienced. Since the introduction of rare earth element Ce and stabilizing element Ti can effectively slow down the oxidation rate, the fracture oxidation degree of the 409L creep specimen containing Ce and Ti is significantly reduced, and the oxide of the fracture of the 409L creep specimen containing Ce and Ti is more dense, because the presence of Ce can improve the density of the oxide layer and the high temperature performance of ferritic stainless steel.
[0052] 3.4 Fracture precipitate analysis
[0053] As shown in Figure 4(b), the degree of hardening of the 409L creep specimen containing Ce and Ti at the end of the first stage of creep is higher than that of the 409L parent material creep specimen. The reason for this phenomenon can be attributed to the pinning effect of Ce element and the effect of solid solution strengthening. On the one hand, the long-term creep plastic deformation of stainless steel mainly depends on dislocation climb, grain boundary voids, and diffusion with the help of vacancies; on the other hand, the nucleation, growth, coarsening and dissolution density of stainless steel precipitates have a great influence on its creep properties. A typical representative is the M generated under long-term high temperature creep conditions. 23 C6 series carburized precipitates, sigma-phase (σ) phase particles and carbon and nitrogen compounds produced during welding.
[0054] Grain boundary morphology and precipitate distribution diagram Figure 9(a) to Figure 9(d) As shown in the figure, the Cr-rich compounds precipitated at the grain boundaries of the 409L base material creep specimen and the 409L creep specimen containing Ce and Ti using the OP loading mode [Figure 9(b) and Figure 9(d)] are obviously coarser and more than those in the corresponding IP loading mode [Figure 9(a) and Figure 9(c)]. In this test, the creep life of the 409L parent material creep specimens and the 409L creep specimens containing Ce and Ti using the OP loading mode is much longer than that of the 409L parent material creep specimens and the 409L creep specimens containing Ce and Ti using the IP loading mode. The creep life of the 409L creep specimens containing Ce and Ti with the addition of Ce and Ti elements is significantly improved under the same test conditions. Therefore, compared with the 409L parent material creep specimens under the same loading mode [Figure 9(a) and Figure 9(b)], the 409L creep specimens containing Ce and Ti have significantly reduced Cr-rich compound content, volume, and grain size.
[0055] The results of the analysis of the boundary precipitates of each 409L base material creep specimen and 409L creep specimen containing Ce and Ti by using an energy dispersive spectrometer (EDS) are as follows: Figure 10(a) to Figure 10(d) shown.
[0056] As shown in Figure 10(a), the grain boundary precipitates of the 409L parent material creep specimen under IP loading mode are more obvious, and the precipitates appear inside the crystal and at the grain boundary, while as shown in Figure 10(b), the grain boundary precipitates of the 409L parent material creep specimen under OP loading mode are distributed along the grain boundary. The main elements of these precipitates are C, Cr, and Fe. It can be inferred that these precipitates are M 23 The series of precipitates such as C6 and M6C and internal chromium-rich compounds such as (Cr, Fe)2O3 and (Fe, Cr)3O4 show that the C and Cr content under OP loading is nearly twice that under IP loading. The main reason for the coarse grain boundary precipitates shown in Figure 10(b) is that M 23 The increase in the content of C6, M6C and other series of precipitates causes the Cr element inside the crystal to segregate at the grain boundaries. 23 There is a certain coherence between the C6 series precipitates and the creep specimen substrate, which is often generated at the grain boundary, which is an important reason for the segregation of Cr in stainless steel. The lack of Cr significantly reduces the acid and alkali corrosion resistance and high temperature oxidation resistance of stainless steel. The promotion of high temperature oxides on crack initiation and expansion is also an important factor affecting creep life.
[0057] Compared with the 409L parent material creep specimen, as shown in Figure 4(a), the creep life of the 409L creep specimen containing Ce and Ti has been significantly optimized in the second stage of the minimum creep rate. As shown in Figures 10(c) and 10(d), the C and Cr contents of the precipitates of the 409L creep specimen containing Ce and Ti have been significantly reduced. With the addition of Ti, which has a high affinity with C, the carbide content will be significantly reduced. Studies have pointed out that a higher Ti / C content ratio also affects M 23 The generation of series of precipitates such as C6 and M6C and the peak value of CSR are the reasons why the 409L creep specimen containing Ce and Ti in Figure 4 (b) shows a higher degree of hardening. In addition, compared with the precipitates of the 409L parent material creep specimen, the content of Mn in the precipitates of the 409L creep specimen containing Ce and Ti has been significantly increased. Mn can be quickly dissolved in oxides such as (Cr, Fe)2O3 and (Fe, Cr)3O4, and produce nodular oxides (Fe, Mn, Cr)3O4 with elements such as Fe and Cr. The addition of Ce can effectively inhibit the loss of Mn, enhance the selective oxidation of Cr, and reduce the propagation of the internal oxidation zone (IOZ). Such synergistic effect is conducive to improving its high temperature oxidation resistance.
[0058] Cr elements will flow to oxides and grain boundaries through dislocation and diffusion in the high temperature environment of creep. Figure 10(a) to Figure 10(d) As shown in the figure, with the extension of high temperature time, the precipitation of Cr element is concentrated from the interior of the crystal to the grain boundary, and finally a Cr-rich internal compound zone is produced along the grain boundary. 23 The C6, M6C and other series of sediments have high temperature sensitivity and are closely related to the duration of high temperature. 23 The increase of C6, M6C and other series of precipitates makes the Cr element segregation phenomenon more obvious. In other words, the main factor affecting the flow of Cr in this experiment is the duration of high temperature. The distribution of Cr elements is obtained by line scanning EDS analysis of the grain boundary precipitates of each 409L parent material creep specimen corresponding to Figure 10(b), Figure 10(c), and Figure 10(d), and the 409L creep specimen containing Ce and Ti, as shown in Figure 11(a), Figure 11(b), and Figure 11(d). As shown in Figure 11(a), the grain boundary of the 409L parent material creep specimen under the OP loading mode is larger, the content of Cr in the precipitates is higher, and obvious segregation behavior occurs, and obvious Cr-poor areas are produced inside the crystal. As shown in Figures 10(d) and 11(d), similar phenomena also occurred in the 409L creep specimens containing Ce and Ti using the OP loading mode, but the Cr and C contents of the grain boundary precipitates of the 409L creep specimens containing Ce and Ti were significantly lower than those of the 409L parent material creep specimens. The reasons have been discussed in the previous section. It can be clearly seen that the precipitation and segregation of Cr in the 409L parent material creep specimens under the IP loading mode are significantly stronger than those of the 409L creep specimens containing Ce and Ti, and as shown in Figures 10(c), 11(b), and 11(c), the Cr content of the 409L creep specimens containing Ce and Ti under the IP loading mode is almost similar to that of the grain boundaries until the final fracture of the crystal.
[0059] In summary, the Cr element begins to precipitate gradually from the interior of the crystal to the grain boundary, and with the continuous high temperature environment, M 23 The generation and increase of C6, M6C and other series of precipitates along the grain boundaries, this precipitation and segregation phenomenon continues to strengthen, and finally gathers at the grain boundaries to form banded compounds. The addition of Ce and Ti elements, Ce pinning, solid solution strengthening can effectively hinder the climb of dislocations, slow down the flow and segregation of Cr from the interior of the crystal to the grain boundary, and the strong affinity of Ti and C effectively hinders the formation of carbon-chromium compounds and delays the loss of Cr inside the crystal, thereby achieving a significant improvement in the creep life of 409L ferritic stainless steel welded joints and the mitigation of the minimum creep rate.
Claims
1. A method for improving the creep properties of 409L stainless steel welded joints, characterized in that: ER304 austenitic stainless steel is used as the filling material for welding, and 0.26% and 1.04% of Ce and Ti elements are added to the welding wire by weight. The Ce and Ti elements are added in the form of nano-scale CeO2 and TiO2, respectively.
2. The method for improving creep properties of 409L stainless steel welded joints according to claim 1, characterized in that: Before welding, the section to be welded of the welding sample is repeatedly cleaned with acetone. After the acetone evaporates, the weight of the two welding samples is weighed, and the acetone solution containing the set mass of CeO2 and TiO2 is evenly applied to the section to be welded. After drying, welding is carried out. After welding is completed, the weight of the welding sample welded as a whole is weighed, and the difference between before and after welding is calculated. Then, the set mass of CeO2 and TiO2 added is divided by the difference, respectively, to obtain a welding sample in which the Ce element and Ti element account for 0.26% and 1.04% of the welding wire mass percentage respectively.